The Ethics of Educator Based on Imam Ghazali’s Perspective: An Analysis of Bidayatul Hidayah Book - Ifendi, Mahfud (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2024)
This article aims to study the concept of educator ethics from Imam Ghazali's perspective as in the book Bidayatul Hidayah and its implications in the world of education. As one of the leading scholars in Islam, he emphasized the importance of ethics in carrying out the duties of an educator with full responsibility and sincerity. This research uses the type of content analysis (library research) with a qualitative approach to explore the ethical values ​​contained in the book with the flow of data condensation, data presentation as well as drawing conclusions. The results of the research show that the ethics of educators according to Imam Ghazali include: responsibility, patience, calm, tawadhu', avoid joking, friendly, thorough, faithful advisor, not easily angered, not embarrassed to say